Students’ Participation in Sport - Students’ Involvement in the Decision Process about Sports Activities (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
The topic of student participation in sport emphasises the importance of the student's role in choosing the sport of choice. The aim of this work is to determine the appearance of children's participation models in the choice of sports. For the purpose of the study, a questionnaire was created to answer questions about participation in sport, focussing on the choice of desired sport. The respondents were primary school pupils in seventh and eighth grade (N=107). The results of this survey confirm the pupils' positive attitude towards sport and a high degree of autonomy in choosing their favourite sport. No differences in participation were found in relation to gender. However, students were not informed about the intensity, dynamics and benefits that sport has for them. The student responses in this study prompted further reflection on the importance of student participation in choosing the sport of choice.